An assessment of the quality of vaccination data produced through smart paper technology in The Gambia. Issue 42 (29th September 2020) - Sowe, Alieu; Gariboldi, Maria Isabella
Abstract: Introduction: MyChild Solution is an innovative Electronic Immunisation Register (EIR) reliant on Smart Paper Technology, thereby eliminating the need for electronic devices and internet connectivity at the point-of-care. The goal of this study is to characterise the quality of routine immunisation data generated using MyChild Solution compared to data obtained through the conventional health management information system (HMIS) used in The Gambia. Method: We used the World Health Organization's (WHO) Data Quality Review (DQR) Toolkit to evaluate MyChild Solution's data quality in the 19 health facilities across two regions implementing MyChild Solution in The Gambia at the time of the evaluation. We evaluated all applicable data quality metrics as well as additional metrics of interest, including the incidence of recording errors, the incidence of incomplete indicator level data, and implausible dates. Where possible, we compared results to those of the conventional HMIS. Results: Both MyChild Solution and the conventional HMIS produced 100% complete and timely data in their reference years. Both systems had no moderate or extreme outliers and showed the expected Penta 1 to Penta 3 dropout direction. However, the proportion of verification factors that are not acceptable was higher in the conventional HMIS. MyChild Solution was found to near perfectly (99.98%) digitise scanned documents. These and other data quality indicators evaluated demonstrate that MyChild Solution produces high quality data with high completeness, timeliness, and consistency compared to the conventional HMIS system. Conclusion: MyChild Solution produces high quality data as per the DQR Toolkit metrics and other metrics of interest of interest. The more internally consitent data produced through MyChild Solution compared to the conventional HMIS demonstrates its potential for supporting data-driven decision-making in immunisation.